Challenges and Capacity Gaps in Smallholder Access to Digital Extension and Advisory Services in Kenya and Uganda - Kansiime, Monica K.; Mugambi, Idah; Rware, Harrison; Alokit, Christine; Aliamo, Caroline; Zhang, Feng; Latzko, Jakob; Puyun, Yang; Karanja, Daniel; Dannie, Romney (Frontiers of Agricultural Science and Engineering, 2022)
An assessment of the challenges and capacity gaps in smallholder access to digital extension and advisory services (EAS) was made by surveying 197 female and 239 male farmers in Kenya and Uganda. Non-digital extension approaches remain dominant but at least 78% of farmers accessed EAS from electronic sources dominated by radio. This is attributed to the fact that ownership of radios was more widespread than of other digital devices. Challenges that particularly limit the use of digital services included low digital literacy and prohibitive cost of internet and mobile devices. Female and elderly farmers were more likely to report these challenges than their counterparts. Logistic regression model results show that ownership of digital devices, participation in post-production activities, and access to extension were enablers of digital EAS use. Farmers mentioned gaps in obtaining information on crop pest/disease diagnosis and management, fertilizer application, pesticide safety and quality seed. Given the diversity in smallholder technological capabilities and information needs, the recommendations made include integration of digital communication within multimode advisory services that use different but linked communication channels, continued farmer digital innovation capacity enhancement, and participatory design approaches that deliver relevant and actionable information for inclusive scaling of extension activities.